Economic evaluation of antibiotic usage for cesarean section in PKU Muhammadiyah Yogyakarta Hospital - Tri Murti Andayani; Riswaka Sudjaswadi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
In the developed countries, the incidence of cesarean section year by year increases by 7 –10 %. There have been various kinds of cesarean section in several hospitals. In PKU Muhammadiyah Yogyakarta hospital, the incidence of cesarean section in 2001 increased up to 21 %. There are also various kinds of antibiotics used to deal with cesarean section cases which caused various kinds of medical cost. Therefore, identification of antibiotics cost, which used to deal with cesarean section in PKU Muhammadiyah Yogyakarta hospital was studied.The study was performed by epidemiological survey of cesarean section via patient’s medical record, medicinal cost for treatment and surgery, and patient’s invoice in the year 2000. The study involved recording identification of patients and physicians identities, antibiotics and other medicines used, surgical equipment, cesarean section indications, pharmacy and other cost, duration of staying related to cesarean section.Results showed that the majority of cesarean section has prolonged labour (26%). The majority of antibiotics used in cesarean section is Sulbenicillin injection with Klindamicin oral (31%) and Amoxicillin/potassium clavulanate injection with Amoxicillin oral (23%). Cost of antibiotics were 12.5% - 44.4% of pharmacy expenses and 6.7% - 14.8% of total expenses. No correlation between antibiotics cost and hospital stays.Key words : cost, antibiotic, cesarean section